DEVELOPING AN ONLINE PLATFORM TO ENHANCE THE COMPETENCIES OF BEING SMART THAIS FOR EDUCATIONAL OPPORTUNITY EXPANSION SCHOOLS - Suebsom, Korawan; Meeplat, Nopparat; Nilwong, Nattaphat; Amiroh, Apinan (Journal of MCU Nakhondhat, 2024)
The research objectives are: to 1) Study the context, background, and problems in schools in order to expand educational opportunities. 2) Develop an online platform to enhance competencies for teachers and students. 3) Assess student competency. The sample group comprised 176 Mathayom 2 students, selected purposively. The tools used in the research include an online platform to enhance the competency of Thai people, competency assessment for thinking skills, and technology use competency assessment, each consisting of 10 questions. The reliability of the assessment was at the levels of 0.847 and 0.853. The statistics used in the research were percentages, averages, and standard deviations. The results of the research revealed the following: 1) The school context expands educational opportunities, are lack of computer equipment and teaching materials, leading to students having limited computer skills. 2) In terms of using online platforms, students expressed the highest level of satisfaction at 67.24 percent ( = 4.57, S.D. = .714). 3) The results of the assessment of thinking competencies and technology use revealed that 50.6 percent ( = 3.75, S.D. = 1.43) believed they could do well in thinking, while 52.8 percent ( = 3.27, S.D. = 1.49) lacked confidence in thinking skills. Additionally, it was found that 39.8 percent of students ( = 3.67, S.D. = 1.23) felt confident in using the Internet for retrieving data and information, while 33.98 percent of students ( = 3.23, S.D. = 1.26) lacked confidence in using technology.